Are national injury prevention and research efforts matching the distribution of injuries across sectors?. (5th March 2014) - Jaldell, Henrik; Ryen, Linda; Sund, Björn; Andersson, Ragnar
Abstract : In 2011, 88% of all unintentional injury fatalities occurred in home and leisure environments in Sweden, while transportation fatalities accounted for 10% and work/school injuries for 2%. The corresponding proportions among non-fatal injuries were 75, 12 and 13%, respectively. However, 83% of the national governmental expenditure on unintentional injury prevention in 2011 was allocated to transportation safety, 7% to home and leisure, and 10% to the work sector including schools. Likewise, around 85% of the governmental research budget aimed for unintentional injury research was allocated to the transportation sector, 9% to home and leisure environments, and 6% to the work and school sector. Our results reveal a striking lack of correspondence between problem profile and governmental countermeasures.